Maximize CdTe solar cell performance through copper activation engineering. (July 2020) - Li, Deng-Bing; Bista, Sandip S.; Song, Zhaoning; Awni, Rasha A.; Subedi, Kamala K.; Shrestha, Niraj; Pradhan, Puja; Chen, Lei; Bastola, Ebin; Grice, Corey R.; Phillips, Adam B.; Heben, Michael J.; et al.
Abstract: The incorporation of copper (Cu) is one of the critical processes for fabricating high-efficiency CdTe thin-film solar cells. However, due to its high mobility in CdTe, the distribution and concentration of Cu must be carefully engineered to reduce the compensative donor-like interstitial defects in CdTe bulk and the recombination centers at the buffer layer/CdTe interface to maximize device performances. Here, a cuprous chloride (CuCl) solution treatment and a rapid thermal annealing (RTA) process are used to control the concentration and distribution of Cu in CdTe absorbers, enabling a champion CdTe thin-film solar cell with a power conversion efficiency of 17.5% without selenium incorporation. The results demonstrate that the use of a CuCl solution can substantially reduce the amount of Cu needed in CdTe and the RTA process is a viable approach to engineer the Cu distribution in CdTe solar cells. Graphical abstract: Image 1 Highlights: Saturated CuCl solution with extremely low Cu concentration is used in CdTe solar cells to subtly control the copper dosage. RTA treatment is used to confine the Cu distribution and suppress the compensative donor-like defects at the front interface. With the mean Cu thickness of 0.19 Å, a champion efficiency of 17.5% is achieved without selenium incorporation.